2019
DOI: 10.3390/ani9070423
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microchip Implantation Events for Dogs and Cats in the VetCompass Australia Database

Abstract: In Australia, compulsory microchipping legislation requires that animals are microchipped before sale or prior to 3 months in the Australian Capital Territory, New South Wales, Queensland and Victoria, and by 6 months in Western Australia and Tasmania. Describing the implementation of microchipping in animals allows the data guardians to identify individual animals presenting to differing veterinary practices over their lifetimes, and to evaluate compliance with legislation. VetCompass Australia (VCA) collates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…This study has revealed that dogs advertised as vaccinated are more likely to be microchipped, suggesting that sellers who take their animals to the vet are more likely to carry out both these procedures, supporting survey findings by McGreevy et al [13]. The thoughts of Rohlf et al [12] on normative beliefs are also supported by this study's findings on Gumtree advertisements; sellers who comply, or pursue "good guardianship" practices, are more likely to comply fully, while those that are either unwilling, or unable to, do not comply at all.…”
Section: Microchippingsupporting
confidence: 87%
See 1 more Smart Citation
“…This study has revealed that dogs advertised as vaccinated are more likely to be microchipped, suggesting that sellers who take their animals to the vet are more likely to carry out both these procedures, supporting survey findings by McGreevy et al [13]. The thoughts of Rohlf et al [12] on normative beliefs are also supported by this study's findings on Gumtree advertisements; sellers who comply, or pursue "good guardianship" practices, are more likely to comply fully, while those that are either unwilling, or unable to, do not comply at all.…”
Section: Microchippingsupporting
confidence: 87%
“…Rohlf, et al [12], have shown microchipping is influenced mostly by the owner's normative beliefs, and non-compliance may be due to the perceived difficulty of microchipping by owners, leading to a recommendation that regulations should require microchipping prior to purchase. The median age of microchipping in Australia is 74.4 days for dogs (just under 11 weeks), and dogs are often microchipped at time of vaccinations [13]. Animal Medicine's Australia's (AMA) 2016 report [2] showed that Victoria had the highest rate of microchipping in Australia, at 89%.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Efforts have been made to optimise the collection of data from primary practice EPRs, such as the development of VetCompass in the UK and Australia, which have facilitated studies with relatively large sample sizes. 14,[16][17][18][19] Pet insurance data allow researchers to obtain large sample populations without the need for primary data collection or utilisation of EPRs from different veterinary clinics. 4,15,20,21 In contrast to EPRswhich provide information on the population presenting for veterinary carepet insurance data also provides information about the background population from the start of insurance enrolment until termination of cover regardless of whether insured animals are seen by a veterinarian or not.…”
mentioning
confidence: 99%
“…The study population represents cats that are accessible for desexing and is expected to comprise cats kept as pets, for breeding, owned by shelters, semi-owned cats and others. Provenance and lifestyle were not investigated because we chose not to collect data from the examination text field in VCA because of its low positive predictive value 57 , and because these data are inconsistently recorded. This precluded the analysis of other variables that may have been related to desexing outcomes such access to outdoors and the number and species of pets.…”
Section: Discussionmentioning
confidence: 99%